‘Candidatus Phytoplasma aurantifolia’ related strains affecting two important medicinal plants (Cymbopogan citratus and Tylophora asthmatica) in India - and G.P. RAO*, MADHUPRIYA, RENU MAURYA (Indian Phytopathology, 2014)
White leaf symptoms in Cymbopogan citratus (lemongrass) (CCWL) and little leaf & yellowing symptoms in Tylophora asthmatica (Antamuula) (TYLL &LY) were recorded in the month of August 2013 at herbal garden of Amity University campus, Manesar, Haryana, India. Total genomic DNA was isolated from symptomatic and non-symptomatic leaf samples of both the plant species and nested PCR was performed using universal primers specific to the phytoplasma 16S rRNA gene: P1/P7 and R16F2/R2n. Expected amplicons size of 1.8kb and 1.2kb were observed from both the symptomatic plant samples in PCR and nested PCR assays, respectively, but not with the non-symptomatic test plant samples. The 1.8 kb amplified PCR products were directly sequenced. BLASTn analysis of the partial 16S rRNA gene sequence of the CCWL and TYLL&LY isolates revealed 99 per cent sequence identity with phytoplasma isolates associated with sesame phyllody, tomato big bud, Echinacea and Scaevola witches’ broom, all members of the peanut witches’ broom phytoplasma (16SrII) group. Phylogenetic analysis of the CCWL and TYLL&LY phytoplasma’s 16S rDNA sequence also revealed their closest phylogenetic relationship with members of the 16SrII group (‘Ca. P. aurantifolia’). This confirms the association of 16Sr II group phytoplasma with CCWL and TYLL&LY diseases in the present study. Virtual and in silico RFLP analysis of 1.25 kb product 16S rRNA gene allowed identification of the phytoplasma into ribosomal subgroup 16Sr II-D in T. asthmatica. However the RFLP profiles in C. citratus indicated different RFLP profiles with Bfa I and Mse I compared to all identified 16S II subgroups. Hence it may be a new subgroup under 16Sr II group which needs further investigation. This is the first report of association of ‘Ca. P. aurantifolia’ affecting C. citratus and T. asthmatica from the world.